Physicochemical and microbiological characteristics of goat milk from animals grown in a mountainous area in Bulgaria - D. Pamukova (Agricultural Science and Technology, 2020)
Abstract. The aim of the study was to determine the goat milk quality from animals grown in a mountainous area in Bulgaria based on physicochemical and microbiological parameters. The study was carried out in a farm that breeds local goats and goats of the Bulgarian White Dairy Goat (BWD). Individual milk samples were taken on a monthly basis from morning milking. A total of 100 individual and 10 bulk milk samples were examined for fat, solids non fat, protein and density. A total of 62 samples were collected at a time to determine the microbiological characteristics of milk. For the period May-September 2017, the percentage of fat in the milk of local goats averaged 3.61% and of goats from BWD goat – 3.54%. The solids non fat were 8.27% and 8.19%, total protein – 3.13% and 3.10%, and the dry matter – 11.89% and 11.74%, respectively. For the period May-August 2017 the individual constituents of milk changed to varying degrees with the most variable being milk fat (decrease of 0.97% in local goats’ milk and 1.09% in milk from BWD goat) followed by solids non fat (0.56% and 0.7%, respectively). The slightest change was in protein – 0.21% and 0.26%, respectively. Coagulase-negative staphylococci were the predominant bacterial species in the goats’ milk samples.